2005
DOI: 10.2337/diabetes.54.12.3410
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Preproinsulin Gene Expression by Leptin Induction of Suppressor of Cytokine Signaling 3 in Pancreatic β-Cells

Abstract: T he hormone leptin is the product of the obese (ob) gene, primarily produced by white adipose tissue (1) and typically circulates in proportion to body fat mass (2). Leptin acts on specific regions in the hypothalamus to inhibit food intake and raise energy expenditure. Elevated leptin levels in obese subjects are believed to be indicative of resistance to leptin. Leptin has also been shown to inhibit insulin secretion and preproinsulin gene expression in pancreatic ␤-cells (3-6), thereby establishing an adip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
71
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 44 publications
4
71
1
2
Order By: Relevance
“…Parallel increases in STAT3 phosphorylation levels ( Fig. S4A) ensured proper leptin signaling under our experimental conditions (20). In contrast, the surface levels of Kir2.1, another inwardly rectifying K + channel in pancreatic β-cells, were not affected by leptin (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Parallel increases in STAT3 phosphorylation levels ( Fig. S4A) ensured proper leptin signaling under our experimental conditions (20). In contrast, the surface levels of Kir2.1, another inwardly rectifying K + channel in pancreatic β-cells, were not affected by leptin (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…It can bind the insulin receptor (IR), impair the phosphorylation of the insulin receptor substrate (IRS)1 and 2 without inhibiting IR phosphorylation, and reduce the expression of IRS1 and IRS2 via a ubiquitin-mediated degradation (9). Furthermore, the overexpression of SOCS3 can also inhibit preproinsulin gene transcription in pancreatic β-cells, which directly reduces insulin secretion (10). Heterozygous SOCS3-deficient mice do not develop insulin resistance when exposed to a high-fat diet (11), whereas a SOCS3 deletion causes embryonic lethality on days 12-16 (12).…”
mentioning
confidence: 99%
“…Thus, SOCS3 has another function in the pancreatic b-cell different from the well-known role as a negative regulator of the JAK/STAT pathway (Fruhbeck 2006). Given that leptin also increases SOCS3 expression in isolated human pancreatic islets and in islets from ob/ob mice treated in vivo, it seems that this mechanism may be general for various species (Laubner et al 2005). Consistent with these findings, SOCS3 mRNA is decreased and proinsulin mRNA is increased in KO mice with a pancreas-specific disruption of the leptin receptor (Morioka et al 2007).…”
Section: Effect Of Leptin On Insulin Gene Expressionmentioning
confidence: 99%
“…Although STAT1, -3, -5b, and -6 are present in INS-1 cells, it seems that leptin-mediated activation of JAK2 recruits basically STAT3 and -5b. Interestingly, it was shown that the inhibitory effect of leptin on insulin gene expression was not mediated by direct interaction of STAT3 or -5b with the proinsulin promoter (Laubner et al 2005). By contrast, leptininduced suppressor of cytokine signaling 3 (SOCS3) expression by STAT-dependent mechanisms was found to be responsible for the inhibition of the rat insulin I gene promoter activity (Laubner et al 2005; Fig.…”
Section: Effect Of Leptin On Insulin Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation